Analisis Empiris Bantuan Asing terhadap Pertumbuhan Ekonomi: Studi Panel ASEAN 2000–2023 - Leony Egista Via; Laudya Ramadhani; Zahra Edyha Cevalonia; Neli Aida; Muhammad Mufti Hudani; Qurrota Ayu Nindien (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to examine the relationship between foreign aid and economic growth in ASEAN countries during the period from 2000 to 2023, using a panel data approach. Data were collected from the World Bank, OECD, and Worldwide Governance Indicators. The results reveal that foreign aid has a positive effect on economic growth, although the impact is statistically limited. The effectiveness of aid is notably stronger in countries with good governance and robust institutional capacity. These findings highlight that foreign aid tends to be more impactful when supported by favorable internal conditions, such as political stability, accountability, and policy reforms. Therefore, beyond increasing the volume of aid, both donors and recipients should prioritize strengthening governance systems to ensure that the economic benefits of aid can be maximized and sustained across the ASEAN region.